2017
DOI: 10.5005/jp-journals-10054-0039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Serum Calcium in Preeclampsia and Normal Pregnancy at Government Medical College and Hospital, Aurangabad City, India

Abstract: Introduction Preeclampsia, a pregnancy-specific disorder, is a global health problem. The major mineral calcium has been proposed to play an important role in the pathogenesis of pre-eclampsia. The present study was aimed to compare the level of serum calcium in normal pregnant women and in preeclampsia and determine the association of serum calcium with severity of the disease. Study design This study included 60 pregnant women diagnosed with preeclampsia as cases and 60 healthy pregnant women as controls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…In another study Paul et al [32] found the mean systolic blood pressure was 145.75±18.44 (mmHg) in preeclamptic patients. Similar observations also observed by Osman et al [35] , Bakacak et al [34] and Dabbaghmanesh et al [46] . In this current study, it was observed that the mean diastolic blood pressure was 97.83±4.85 mmHg.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In another study Paul et al [32] found the mean systolic blood pressure was 145.75±18.44 (mmHg) in preeclamptic patients. Similar observations also observed by Osman et al [35] , Bakacak et al [34] and Dabbaghmanesh et al [46] . In this current study, it was observed that the mean diastolic blood pressure was 97.83±4.85 mmHg.…”
Section: Discussionsupporting
confidence: 87%
“…Abnormal placentation in preeclampsia leads to decreased activation, increased catabolism, and impaired placental uptake of vitamin D and is unable to produce sufficient levels of 1,25-(OH)2 vitamin D [33] . In this present study, it was observed that [34] obtained in their study that ~ 94 ~ vitamin D levels were lower in preeclamptic patients compared to healthy normotensive pregnant women (p<0.001). Vitamin D supplementation is considered to decrease the risk of preeclampsia in the patient population at risk for vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations